Analisis Zat Warna Sintetik Terlarang Untuk Makanan Yang Beredar Di Pasaran - Azizahwati, Azizahwati; Kurniadi, Maryati; Hidayati, Heidi (Majalah Ilmu Kefarmasian, 2007)
The use of synthetic food colorants is increasing because of its advantages. However, it is found that not all food colorants which are sold in the market are safe to be consumed. The purpose of this research was to identify synthetic food colorant samples which are sold in market and to find out whether they contain safe food colorants or not. Extraction did not need to be done on samples. Analysis was done using color reaction and paper chromatography. Densitometry was done to support the identification result. The result of this research showed that 10 out of 31 samples that were tested contain synthetic food colorants that must not be used for food. The ten samples were seven red colorants (three samples containing Merah K4, the two others containing Rhodamine B, and two samples containing Scarlet GN), one orange colorant (containing Orange G), one yellow colorant (containing Metanil Yellow) and one chocolate colorant (containing Chocolate Brown FB).